Letter from Lieutenant Commander J. D. Marvin to James Curtis Booth, February 2, 1872 - Marvin, J. D. (1872)
Lieutenant Commander J. D. Marvin follows up with James Curtis Booth (1810-1888) from his letter of January 12 about the use of silver or copper in ordinance experiments at DuPont’s Powder Mill. Marvin asks for more details on the preparation of the silver disks recommended by Booth.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; E.I. du Pont de Nemours & Company; Marvin, J. D.